A water-activated battery based on activated carbon - Dang Trang Nguyen; Kozo Taguchi (International Journal of Electrical and Computer Engineering (IJECE), 2019)
In this research, a novel property of activated carbon powder (AC powder) has been utilized to realize a disposable paper-based battery. AC powder was loaded on a 3D carbon paper substrate to make the anode. The cathode was integrated directly on the paper-based battery case by coating multiwalled carbon nanotube mixed with potassium ferricyanide on a side of a sheet of filter paper, the other side worked as a paper-based proton exchange membrane. This design provides a simple but practical disposable water-activated battery. The developed battery generated the maximum power density of 10.4 µW/cm2 at the AC powder concentration of 17 mg/cm2. Although, the output power of the battery is low, it is made of low-cost and abundant materials, and therefore being able to scale up. The battery is a disposable and on-demand micropower generation activated anytime, anywhere by water.